Contrasting regional versus global radiative forcing by megacity pollution emissions. (October 2015) - Dang, H.; Unger, N.
Abstract: We assess the regional and global integrated radiative forcing on 20- and 100-year time horizons caused by a one-year pulse of present day pollution emissions from 10 megacity areas: Los Angeles, Mexico City, New York City, Sao Paulo, Lagos, Cairo, New Delhi, Beijing, Shanghai and Manila. The assessment includes well-mixed greenhouse gases: carbon dioxide (CO2 ), nitrous oxide (N2 O), methane (CH4 ); and short-lived climate forcers: tropospheric ozone (O3 ) and fine mode aerosol particles (sulfate, nitrate, black carbon, primary and secondary organic aerosol). All megacities contribute net global warming on both time horizons. Most of the 10 megacity areas exert a net negative effect on their own regional radiation budget that is 10–100 times larger in magnitude than their global radiative effects. Of the cities examined, Beijing, New Delhi, Shanghai and New York contribute most to global warming with values ranging from +0.03 to 0.05 Wm −2 yr on short timescales and +0.07–0.10 Wm −2 yr on long timescales. Regional net 20-year radiative effects are largest for Mexico City (−0.84 Wm −2 yr) and Beijing (−0.78 Wm −2 yr). Megacity reduction of non-CH4 O3 precursors to improve air quality offers zero co-benefits to global climate. Megacity reduction of aerosols to improve air quality offers co-benefits to the regional radiative budget but minimal or no co-benefits to global climate with the exception of black carbon reductions in a few cities, especially Beijing and New Delhi. Results suggest that air pollution and global climate change mitigation can be treated as separate environmental issues in policy at the megacity level with the exception of CH4 action. Individual megacity reduction of CO2 and CH4 emissions can mitigate global warming and therefore offers climate safety improvements to the entire planet. Highlights: Apply a global chemistry-climate model to study impacts of megacity emissions. Quantify multi-pollutant climate effects of ten megacity regions. Calculate integrated radiative forcing metric on two time horizons. Combined pollution emissions from megacities contribute to net global warming. Ozone and aerosols from megacity regions have minor or no effects on global climate.